Pengaruh Pelatihan Komunikasi Efektif terhadap Caring Perawat di Ruang Rawat Inap Rumah Sakit Umum Bali Royal - Anak Agung Ayu Sri Suwitri; Alfiery Leda Kio; I Gede Wirajaya (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2020)
Caring is a factor that affects the quality of nursing services and patient satisfaction. Caring behavior is not innate, but can be learned and practiced. Communication as a basic capital in caring behavior, it is very important to provide effective communication training or therapeutic communication to all nurses. This study aimed at determine the effect of effective communication training towards nurse caring in the ward at Bali Royal Hospital. The research method used is quantitative with Pre-Experimental One-Group Pretest-Postest Design. The research sample consisted of 50 nurses in the ward at Bali Royal Bali Hospital with a purposive sampling technique. Data were collected using a questionnaire and analyzed using the Wilcoxon Signed Rank Test statistic test. The results of the study were obtained from 50 respondents, the majority of respondents experienced an increase in caring behavior after the intervention/ treatment of effective communication training as many as 49 people and the results of statistical tests showed that there was an effect of effective communication training towards caring nurses in ward at Royal Bali Hospital. Suggestions to nurses to improve the ability of caring behavior to increase patient satisfaction with services. Nurses should actively participate in training and be active in finding information related to caring behavior.